TIPOLOGI ORGANISASI RUANG DAN ELEMEN INTERIOR RUMAH ABU HAN DI SURABAYA - C. Indrani, Hedy; Prasodjo, Maria Ernawati (Institute of Research and Community Outreach - Petra Christian University, 2005)
Surabaya has three ancestral houses that located on jalan Karet. Ancestral house of Han family has been chosen as the object of study because it is the oldest, the biggest, the building is physically still sound and in good condition. The architecture of the building and the interior elements of the house as a whole show the existence of harmonious unity among elements of Chinese style, Dutch colonial and Javanese style. It reflects the social and culture values, owner life style and the local community condition. Climate condition and natural environment also influence the architectural element of building. Abstract in Bahasa Indonesia : Surabaya memiliki tiga buah rumah abu yang terletak di jalan Karet. Rumah abu keluarga Han terpilih sebagai objek studi karena merupakan rumah abu tertua, terbesar, fisik bangunan masih utuh dan dalam kondisi terpelihara dengan baik. Arsitektur bangunan dan elemen interior rumah secara keseluruhan memperlihatkan perpaduan harmonis antara unsur gaya Cina, kolonial Belanda dan Jawa. Hal ini sebagai refleksi nilai sosial, budaya, gaya hidup pemilik serta kondisi masyarakat setempat. Kondisi iklim dan lingkungan sekitar juga ikut mempengaruhi kondisi elemen arsitektur bangunan Kata kunci: rumah abu Han, elemen-elemen interior, dan pengaruh budaya.